Repair By Venovenostomy Between Cephalic Vein and Axillary Vein in Proximal Cephalic Vein Stenosis at Brachiocephalic Arteriovenous Fistula - Baris Akin Murat Dayangac, Emin; Taner, Burcin; Tokat, Yaman (Annals of Medical Research, 2021)
None